A Study On Determinants Of Rfid Adoption Intention Among Hajj Organizers In Indonesia And Malaysia And Its Strategic Information Systems Plan - Al-Hashedi, Abdullah Hussein Ahmed (2013)
Every year, millions of Muslims go to Makkah to perform the Hajj (Pilgrimage). The management of Hajj activities is a very complex task for Saudi Arabian authorities and Hajj organizers because of the large number of pilgrims, the limited geographical area for pilgrim movement, and the short Hajj period. Radio frequency identification (RFID) technology can be used to provide good solutions for the problems and difficulties that arise during Hajj season. However, as an emerging technology, the use of RFID in Hajj management has not been investigated till date. This study develops a theoretical model for RFID adoption intention in Hajj organizations by using the technology–organization–environment framework. Seven independent variables (relative advantage, compatibility, complexity, top management support, organization size, government support, and willingness to collaborate among partners) and one moderator variable (organizational readiness) are proposed to help predict the RFID adoption intention. The variable of willingness to collaborate among partners, which has been ignored in previous Information Systems literature, is included in this study as an important factor in the environmental context. This study empirically tests the proposed model by using an adequate sample size of Hajj organizations. Data collected from 165 Hajj organizers from Indonesia and Malaysia and their Hajj service provider in Saudi Arabia are tested against the proposed research model using hierarchical regression.